2004
DOI: 10.1002/jmri.20144
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative evaluation of metal artifact reduction techniques

Abstract: Purpose: To develop a technique to quantify artifact, and to use it to compare the effectiveness of several approaches to metal artifact reduction, including view angle tilting and increasing the slice select and image bandwidths (BWs), in terms of metal artifact reduction, noise, and blur. Materials and Methods:Nonmetallic replicas of two metal implants (stainless steel and titanium/chromium-cobalt femoral prostheses) were fabricated from wax, and MR images were obtained of each component immersed in water. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
65
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(66 citation statements)
references
References 11 publications
1
65
0
Order By: Relevance
“…This study demonstrated that VAT and SEMAC-VAT, previously utilized at 1.5 T, 16 can be adapted to 3.0 T with similar success. Farrelly et al 20 found, in a phantom model, reductions in artefact severity with longer readout bandwidths with better overall image quality at 3.0 T. In addition to bandwidth considerations, previous work on improving MRI around metal implants has also focused on VAT techniques originally described by Cho et al 13 Kolind et al 21 also described a VAT SE sequence utilizing high RF and readout bandwidths. This sequence was referred to as a "metal artefact reduction sequence".…”
Section: Discussionmentioning
confidence: 99%
“…This study demonstrated that VAT and SEMAC-VAT, previously utilized at 1.5 T, 16 can be adapted to 3.0 T with similar success. Farrelly et al 20 found, in a phantom model, reductions in artefact severity with longer readout bandwidths with better overall image quality at 3.0 T. In addition to bandwidth considerations, previous work on improving MRI around metal implants has also focused on VAT techniques originally described by Cho et al 13 Kolind et al 21 also described a VAT SE sequence utilizing high RF and readout bandwidths. This sequence was referred to as a "metal artefact reduction sequence".…”
Section: Discussionmentioning
confidence: 99%
“…More objective phantom-based methods can be useful for systematic comparison of different pulse sequences and for protocol optimization. Methods of varying complexity have been proposed, most of them measuring the total size of the artifact [12,13,14,15]. Recently, Koff et al proposed a method which separates through-plane and in-plane artifacts; however it was restricted to investigation of metallic objects of a fixed, cylindrical shape [16].…”
Section: Evaluation Of Artifacts In Mri Of Metal Prosthesesmentioning
confidence: 99%
“…An off-resonance in the kilohertz range could potentially translate to prominent image distortion in both the frequency encoding direction (in plane) and the sectionselect direction (through plane). Image distortions due to the presence of metallic implants have been addressed by numerous techniques (17)(18)(19)(20)(21). The most widely used are multiacquisition variable-resonance image combination, or MAVRIC (22), and slice encoding for metal artifact correction, or SEMAC (23).…”
Section: Technical Developments: Improved Lge Mr Imaging In Patients mentioning
confidence: 99%